Application of Artificial Intelligence Technology in the Eradication of Corruption Criminal Acts in Indonesia - Harris, Nadief Rahman; Wicaksana Prakasa, Satria Unggul (Faculty of Law, University of Muhammadiyaha Surabaya, 2022)
Countries in the world are currently moving towards Â to the development of sophisticated intelligent automated systems including the State of Indonesia where this system is able to achieve digital transformation which is considered as one of the most important pillars of modern economic growth. Â With the PBB's call to implement the 2030 sustainable development plan, right in the context of this transformation, countries including Indonesia are trying to utilize modern technology in combating many issues that haunt society, namely corruption. The researcher will answer the questions (1) The legitimacy of the use of AI by the KPK in the Eradication of Corruption in Indonesia (2) The ideal legal mechanism to accommodate the use of artificial intelligence technology in eradicating corruption in Indonesia. This research uses a sociolegal approach. The results in this study indicate that in the legitimacy of the KPK in eradicating corruption criminal acts by using artificial intelligence products for eradicating corruption criminal acts, there are several articles that can be reviewed that the importance of the KPK is to use technology products in eradicating corruption criminal acts and the use of technology in handling evidence collection. and strengthen the evidence that states the existence of Â corruption acts